The Green Economy Research Centre – positioning geographical research in Aberdeen to address the challenges of green economy transitions. (2nd October 2019) - Potts, T.; Niewiadomski, P.; Prager, K.
ABSTRACT: The necessity to address climate change has resulted in a widespread debate about the need for a transition to a 'greener' economy. How such an economy emerges, by what drivers and at what scale is a significant source of speculation amongst the geographical research community. In the context of longstanding contributions to environmental geography from scholars working at Aberdeen University, this paper outlines a novel research agenda for the Green Economy Research Centre (GERC). The contours of the green economy are examined in the context of economic sectors of food production, tourism, energy and the blue economy. Cross-cutting themes of green transitions, governance, people and place and ecosystem services inform our academic contribution to this evolving and controversial societal issue.